Less politicking and more thinking is needed to revive the Islamic civilization - Abdul Razak, Mohd. Abbas; Rahath House, Yousef; Abd. Razak, Abdul Latif (Zes Rokman Resources, 2016)
Prior to the advent of the Prophet of Islam, Arabia was engulfed in the Days of Ignorance (Ayyamul Jahiliyyah). The degrading lifestyle and barbarism of the Arabs kept the superpowers of that time; Rome and Persia away from ruling Arabia. It was deemed by the superpowers that to rule Arabia would be a total liability on their side. This scenariochanged with the coming of Prophet Muhammad. His prophethood marked the emergence of a new era in the lives of the Arabs. It was a birth from darkness into light. The teachings of the Qur’an and the tradition (Sunnah) of Prophet took the Arabs out from their degrading lifestyle into one which is filled with enlightenment, dynamism and spirituality. Within a short period of time, the Islamic teachings transformed the lifestyle of the Arabs into one which is full of virtue, high moral values, spirituality, etc. From strength to strength the Muslims and their civilization grew and gave rise to the establishment of many empires. At the peak of their civilization (750-1258), Muslims scholars and scientists became great authorities in the many fields of revealed,natural and human sciences. All the fame and glory of the Islamic civilization started to decline with the fall of Baghdad in 1258 when it was attacked by the Mongols. From that point in history to the eras of Western colonization of Muslim lands and European Industrial Revolution, Muslims seems to have lost the dynamism they once had in the areas of science, technology, creative and critical thinking. At the moment, though all Muslims countries have got their independence and many are blessed with wealth in the form of oil and gas, many are not doing well in terms of having political stability and sustainable development. This research is directed towards calling the Muslim Ummah to relook into their chaos, political instability, extremism, sectarian wars,brain drain, etc. Upon reassessing the present conditions in their countries, Muslims must work towards restoring their lost dynamism of the past.